If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -0.2(-15x + -10) = 10 Reorder the terms: -0.2(-10 + -15x) = 10 (-10 * -0.2 + -15x * -0.2) = 10 (2 + 3x) = 10 Solving 2 + 3x = 10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 3x = 10 + -2 Combine like terms: 2 + -2 = 0 0 + 3x = 10 + -2 3x = 10 + -2 Combine like terms: 10 + -2 = 8 3x = 8 Divide each side by '3'. x = 2.666666667 Simplifying x = 2.666666667
| -7(4)+15=x | | z(2z-9)(z+4)=0 | | x^2+kx-9=0 | | 5=4(x-4)+3-3x | | 30+y=3y | | 12x+4+13x-4=180 | | (m-1)x^2+mx+2m=0 | | n+(n+1)+(n+2)+(n+3)=1368 | | 30+y=6y | | 6x+8-5x=14-15x-16 | | 6x/5+12x=3(5/2) | | 3b^2+20b+31=6 | | x^4+10x^3-59x^2+40x+60=0 | | 12y-8=-4 | | 34x-543=321 | | 2x-34=87 | | 29x^2+10x-21=0 | | 3=3(x-2)+5-2x | | (14y+11)+(-4y-3)= | | 15=5(x+9) | | 13p+16q+p-5q-7p= | | 2x(4x-1)=7 | | (14y+11)+(14y-3)= | | 5-9x=35-23x | | D=Bgx | | 0.8x+6.7=2.3 | | -6x+19+8x+19=-6 | | 10(x+2)=2(x+10) | | (2x-1)(x^2+4x-4)= | | 0.24x^2-2.4x+4=0 | | 4[2q-2]=16q | | 18-2x=-4+12 |